Associations between attachment, therapeutic alliance, and engagement in black people with psychosis living in the UK. (3rd September 2022) - Degnan, Amy; Shattock, Lucy; Edge, Dawn; Muller, Claire; Berry, Katherine
Abstract: Background: Compared to other ethnic groups in the UK, Black people have the highest rates of psychosis. This may partly be explained by both assessment bias and structural racism. Mental health services often find it difficult to develop therapeutic relationships with Black people with psychosis. Attachment theory posits that the quality of previous caregiving experiences influence current interpersonal functioning and emotional regulation. In this study, we applied the theory to improve the understanding of therapeutic relationships with people with psychosis. Aims: This is the first study to examine associations between attachment difficulties, therapeutic alliance, and service engagement in a Black sample with psychosis. Method: Fifty-one participants completed self-report measures of attachment and alliance. Staff completed measures of alliance and service engagement. Results: Higher attachment avoidance was related to poorer alliance ratings. These significant findings were not upheld in a regression model controlling for total symptom scores and perceived ethnic/racial discrimination in services. Attachment anxiety was generally not associated with alliance ratings. Neither attachment anxiety nor attachment avoidance was significantly associated with service engagement. Conclusions: Staff should be supported to better understand the needs of service users with avoidant attachment behaviours and to develop mutually-agreed treatment goals and therapeutic bonds.